Mechanical properties of hybrid sisal/glass fiber mats reinforced hot cured saturated cyclic epoxy resin EPR-760 composite. - Diệu, Trần Vĩnh; Ngọc, Phan Thị Minh; Thành, Nguyễn Đắc; Linh, Nguyễn Phạm Duy; Nhàn, Nguyễn Thị Thanh (Vietnam Journal of Chemistry, 2012)
This paper shows the research results of mechanical properties of hybrid sisal/glass fiber mats reinforced hot cured saturated cyclic epoxy resin EPR760 composites. Mechanical properties of obtained composites are higher in comparison with those of virgin epoxy resin, especially in impact strength is 67% higher. The effect of alkali treatment (NaOH 0.1 N, 72 hours, at room temperature) of sisal fiber on the interfacial shear strength (IFSS) and mechanical properties of composites were studied. It was shown that average IFSS of treated fiber is 135% higher; tensile strength, flexural strength and impact strength of treated fibers are 151%, 110% and 55% respectively higher than those of untreated fibers. In order to improve mechanical properties of composites, sisal fiber mat was replaced partly by glass fiber mat (hybridization). Owing to the superior properties of glass fibers, the mechanical properties of the hybrid composites increase with the increasing of weight fraction of glass fiber. The observation has shown that optimum glass fiber loading for the hybrid composite was 50wt%. The effect of sisal fiber content on mechanical properties of composites was investigated. The most effective content of sisal fiber was 45wt%. Scanning electron microscopic studies were carried out to estimate the fiber-matrix adhesion.